Learning in Primary-First-to-Sixth Grade Students about Reading and Mathematics and the Need to Correct the National Curriculum of Studies - León, Federico R. (2016)
In his recent review of the national research on the education field, Rodriguez (2013) identified six general subjects that, in order of volume and productive wealth, seem to differentiate the first category-factors associated with school performance and attendance from the following categories: teacher training, teaching practices and classroom performance, learning resources, decentralization of education management and participation, funding and returns to education.